Determinasi kinerja ekonomi kawasan ekonomi khusus di Pulau Sumatera: Bukti dari empat KEK - Yessi Tamba; Puti Andiny; Miswar Miswar (Nur Science Institute, 2025)
This study aims to analyze the factors influencing the economic performance of Special Economic Zones (SEZs) on Sumatra Island, focusing on the Sei Mangkei SEZ, Galang Batang SEZ, Tanjung Kelayang SEZ, and Arun Lhokseumawe SEZ over the 2019–2023 period. The data are examined using a panel regression model with Gross Regional Domestic Product (GRDP) as the dependent variable and two independent variables: investment and the Labor Force Participation Rate (LFPR). The estimation results show that investment has a positive and statistically significant effect on GRDP, indicating that it is the primary driver of economic growth in Sumatra’s SEZs. In contrast, the LFPR does not have a statistically significant effect on GRDP during the study period. These findings suggest that improving the investment climate and increasing realized investment are critical to strengthening SEZ economic performance. A limitation of this study is that it covers only four SEZs; future research should expand the sample to include additional SEZs and incorporate other relevant variables to provide a more representative assessment of SEZ development on Sumatra.